Identification and Reduction of Bitter Taste Determinant Compounds in Chocolate Spread Formulated with Candlenut - Zenita Mulya Astuti; Dwi Larasatie Nur Fibri; Siham Ayouaz; Dimas Rahadian Aji Muhammad (Universitas Sebelas Maret, 2024)
Candlenuts can be used as a substitute in producing chocolate spread due to their high-fat content. However, the limitation of using candlenut in the spread formulation is the existence of a bitter taste. This study aimed to investigate the effect of sodium bisulfite and sodium bicarbonate soaking treatment (100, 300, and 500 ppm) on reducing the bitter taste of candlenut seed. In order to reach the goal, bitter compounds of candlenut and chocolate spread were identified using Liquid chromatography-mass spectrometry (LC-MS). The sensory characteristics of chocolate spread were profiled using the Rate All That Apply (RATA) descriptive method. It was shown that the panelists identified 14 sensory attributes in the samples, one of which was bitter taste. Treatment with sodium bisulfite, as well as sodium bicarbonate at the level of 300 ppm, reduced the intensity of the bitter taste. The treatment reduced flavonoid and tannin levels by 85.21% and 82.08% in candlenut seeds. It also reduced flavonoid and tannin levels by 88.47% and 72.71% in chocolate spread, respectively. LC-MS identified 13 compounds that cause the bitter taste, namely quercetin, oleuropein, kaemferol, resveratrol dimer, luteolin, epicatechin, theobromine, caffeine, iso-humolones, colaflavone, chlorogenic acid, feruloyl-caffeoylquinic acid, and coumaroylquinic acid. This study creates a new technique for producing chocolate spread formulated with candlenuts with lower bitterness levels.